Assessment of water quality and genotoxic impact by toxic metals in Geophagus brasiliensis. (June 2016) - Morais, Cássio Resende; Carvalho, Stephan Malfitano; Araujo, Galber Rodrigues; Souto, Henrique Nazareth; Bonetti, Ana Maria; Morelli, Sandra; Campos Júnior, Edimar Olegário
Abstract: This study used the pearl cichlid Geophagus brasiliensis as a bioindicator to survey the health of the aquatic environment on four sites (P1, P2, P3 and P4) of the Mumbuca stream located at Monte Carmelo/MG, Brazil. The selection of different sites was made with reference to the gradient of urban activity and via physicochemical and biological evaluation of water quality and genotoxicity. The water quality index was classified as 'good' for P1 and P4, regular in P2 and 'poor' for P3. The micronuclei (MN) frequency obtained from blood analysis was in agreement with the water quality, such that the higher values of MN were detected in sites evaluated as poor. Water degradation conditions worsen according to the flow of the stream over the sites P1, P2 and P3, but for site P4, located after the Monte Carmelo Sewage Treatment Plant, improvements in the micronuclei frequency are detected. Our results showed high levels of potentially toxic metals (chromium, lead, aluminum and nickel) in specific stream sites (P2 and P3). We suggest that the micronuclei induction in G. brasiliensis could be due to the presence of these compounds. Highlights: The genotoxic potential was studied on Mumbuca river. The Mumbuca stream is the target of different anthropic contaminants. Toxic metals (Cr, Pb, Al and Ni) were identified and should be the responsible for DNA damage in Geophagus brasiliensis . G. brasiliensis is an excellent indicator of environmental impacts in water bodies.